Pengaruh proses pembelajaran kepada prestasi kerja ekspatriat - Nur Syahirah, Mad Rosli (2023)
International human resource management is expanding because of rising worldwide competitiveness and the internationalization of the global market. The increasing number of expatriates has contributed to the process of internationalization which acts as one of the main factors to the sharing of knowledge and ideas through international assignments. In order to improve the expatriate’s function in international assignments, it is important to practice effective strategies to ensure that the expatriate plays an optimal role. Therefore, this study was conducted to identify the influence of the learning process on the work performance of expatriates. The objective of this study is to identify the factors that influence the learning process of expatriates from international assignments, examine the host company’s responsibility towards the expatriate learning process and explain the influence of the learning process during international assignments on expatriate work performance. This study uses qualitative methods to obtain data through open-ended questions given to respondents consisting of 7 foreign expatriates who work in multinational companies from various sectors in Malaysia. The findings of this study explain that the expatriate learning process is influenced by 4 factors, namely expatriate preparation, learning orientation, cultural intelligence and work performance evaluation. Additionally, the implication of this study helps to provide the guide to develop the international trade and business sector which is closely related to the flow of goods and services, capital, technology, human resources and knowledge sharing between two countries. Future research should focus on the influence of the entire learning process on expatriates by identifying the appropriate learning process to be used in helping expatriates to adapt and improve expatriate performance.